Characteristics and surgical outcomes of patients with atraumatic splenic rupture. Issue 2 (February 2022) - Colak, Elif; Ciftci, Ahmet Burak
Objective: Although rare, late-diagnosed atraumatic splenic rupture (ASR) may result in mortality. We investigated the occurrence of ASR cases at our centre over the previous six years. Methods: This was a retrospective, cross-sectional study that included all patients who underwent emergency splenectomy due to ASR between January 01, 2015, and January 01, 2021. Results: Of the 203 patients who underwent splenectomy, 15 met our criteria for ASR. Median age was 55 years (34–90), and 10 (67%) patients were male. Most common pre-existing diseases were diabetes mellitus (6, 40%) and heart valve disease (5, 33%). Ten (67%) patients had splenic rupture due to splenic infarction and abscess. There were two (13%) cases with diffuse large B cell lymphoma (DLBCL) and two (13%) cases with lung cancer and spleen metastasis. Median length of hospital stay was 6 days (2–24) and three (20%) patients died in hospital. Conclusions: Male sex, previous splenic infarctions, haematological malignancies, lung cancer spleen metastases, underlying cardiovascular disease and diabetes mellitus may increase the risk for ASR. Further prospective controlled studies are needed to confirm our results.